2010
DOI: 10.1182/blood-2009-09-241547
|View full text |Cite
|
Sign up to set email alerts
|

Expression of terminal α2-6–linked sialic acid on von Willebrand factor specifically enhances proteolysis by ADAMTS13

Abstract: von Willebrand factor (VWF) multimeric composition is regulated in plasma by ADAMTS13. VWF deglycosylation enhances proteolysis by ADAMTS13. In this study, the role of terminal sialic acid residues on VWF glycans in mediating proteolysis by ADAMTS13 was investigated. Quantification and distribution of VWF sialylation was examined by sequential digestion and high-performance liquid chromatography analysis. Total sialic acid expression on VWF was 167nmol/ mg, of which the majority (80.1%) was present on N-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 49 publications
(85 reference statements)
2
91
0
3
Order By: Relevance
“…11,14 In recent studies, we and others have clearly demonstrated the key role played by VWF glycans in regulating proteolysis by ADAMTS13. [15][16][17][18] Importantly, expression of both ABO blood group antigens and terminal sialic acid on VWF were shown to be of critical importance. 15,16,18 In this study, we have characterized terminal carbohydrate expression on platelet-VWF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,14 In recent studies, we and others have clearly demonstrated the key role played by VWF glycans in regulating proteolysis by ADAMTS13. [15][16][17][18] Importantly, expression of both ABO blood group antigens and terminal sialic acid on VWF were shown to be of critical importance. 15,16,18 In this study, we have characterized terminal carbohydrate expression on platelet-VWF.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Importantly, expression of both ABO blood group antigens and terminal sialic acid on VWF were shown to be of critical importance. 15,16,18 In this study, we have characterized terminal carbohydrate expression on platelet-VWF. Our findings demonstrate that platelet-VWF exists as a distinct natural glycoform, with a particular marked reduction in N-linked sialic acid expression compared with plasma-VWF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,[9][10][11] Although the O-linked glycans of VWF also demonstrate marked heterogeneity, disialyl core 1 structures account for ;70% of the total population. 8,12 Importantly, although the majority of its glycans are capped by negatively charged sialic acid, 7,13 VWF is unusual in that a minority of both N-linked and O-linked carbohydrate chains express terminal ABO(H) blood group determinants. 7,8,11 Although substantial progress has been achieved in understanding the biosynthesis, structure, and functions of VWF, the biological mechanism(s) responsible for modulating VWF clearance from the plasma remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clarified this association and verified that B and A1 blood groups are at higher risk than O and A2 blood groups, with the relative risk of approximately 2 (38,39). It is assumed that an ABO blood group could contribute to thrombosis risk through modifications of von Willebrand factor (VWF) and factor VIII (FVIII) levels in plasma (40,41). On the other hand, several studies have revealed that ABO blood groups remain significantly associated with elevated prothrombotic risk, even after adjustment for FVIII or VWF levels (41,42).…”
Section: Other Genetic Risk Factorsmentioning
confidence: 99%